Risk contagion in the cross-border banking network: Some new evidence - Chen, B.; Li, L.; Peng, F.; Salim, Ruhul (Wiley-Blackwell, 2019)
This paper applies consolidated banking statistics data from the Bank for International Settlement to simulate risk contagion in a cross-border banking system with shocks of credit and liquidity. Simulation results from balance sheet network analysis show that the banking systems of the United States and the United Kingdom are the most systemically important systems under the credit shocks in June 2008. Moreover, banking system's counter-shocks ability is directly related to its size and concentration of foreign claims. The banking systems of German and French are the most systemically important systems under liquidity shocks. Some banking systems depend heavily on German and French banking systems for financing and are vulnerable to liquidity shocks. Risk transfer has influence on risk contagion in the cross-border banking system. After the subprime crisis, cross-border risk contagion has declined because of deleveraging foreign claims. Raising the capital level of the banking system or intervention in the interbank market to enhance the liquidity of the market under pressure scenarios can reduce the contagion effect of credit or liquidity shocks.